Developing Future Teachers’ Information Competence in Inclusive Education: A Comparative Study of Uzbekistan and Indonesia within the WFIEd Framework - Dustnazar Omonovich Khimmataliev; Nilufar Parda Qizi Omonova (PT. Pusmedia Group Indonesia, 2026)
This study investigates the development of future teachers’ information competence in inclusive education settings through a comparative analysis of Uzbekistan and Indonesia. Information competence is conceptualized as an integrative construct comprising cognitive, operational–practical, motivational–value, and reflective components. Using theoretical analysis and comparative pedagogy methods, the research highlights significant differences between national teacher education models. The Indonesian experience, particularly the reflective–research-based approach advanced by Professor Ediyanto Ediyanto at Universitas Negeri Malang, demonstrates a systematic integration of information analysis, adaptation, and pedagogical decision-making. The WFIEd framework is positioned as a mechanism for international methodological alignment. Based on the findings, the article proposes evidence-based recommendations for improving methodologies for developing information competence among future teachers in inclusive education contexts.